Examination of flexibility and sprint performance values of adolescent footballers - Bekir Mentes; Kenan Uzun; Tuncay Ercın (Türk Spor ve Egzersiz Dergisi)
The flexibility is effective to provide an optimal body development appropriate to needs of sports branch and development of physical factors such as strength, speed and sport technique. The purpose of this study is to compare the flexibility and sprint performance values according to age and gender, the features of physical fitness performance of boys and girls who play football. Total of 172 volunteer’s measurements were evaluated which consisted of 99 men footballer whose average age are 12,919 0,078 years and 72 women footballer whose average age are 12,973 0,065 years. Age, height, weight, BMI, flexibility, 10 m and 20 m speed measurements of groups were taken. Multiple Regression Analysis was utilized for searching the relationships between flexibility and detected features. Formed by Stepwise variable selection method, the Multiple Regression Analysis was allowed to consist of statistically significant variables. Two sample T-test was used to compare gender in terms of average speed of 10 m and 20m. 10 m and 20 m sprint performance determined that the significant difference is in favor of the male players according to gender. The relationship between speed and flexibility was varied by gender. The significant relation was found between flexibility values and 10 m sprint performance values of male footballers (P=0,002), while the significant relation was found between flexibility values and 20 m sprint performance values of female footballers (P=0,009).In order to improve the sprint performance, which is a specific skill of football, flexibility of the muscles should be trained with a program at an early age.